LEGAL ISSUES OF AUDIO-VIDEO RECORDING IN MEDICAL ORGANIZATIONS - Артымук, Владимир Анатольевич; Черняева, Марина Анатольевна; Шемет, Ярослав Игоревич; Артымук, Наталья Владимировна; Черняева, Валентина Ивановна (Mother and Baby in Kuzbass, 2019)
The aim of the study was to analyze the regulatory framework for audio and video recording in a medical organization.Materials and methods. The analysis of modern scientific literature, as well as regulatory on the legality of conducting audio and video recordings in a medical organization by a patient, a medical organization and a medical worker is carried out. The study analyzed the current legislation of the Russian Federation, the judicial practice of the High Courts of the Russian Federation and courts of general jurisdiction in order to determine the boundaries of the right field, when and by whom in the process of providing medical care it is possible to carry out audio or video fixation legally, and is it possible, based on the law, ban it.Conclusion. The results of the study determined the regulatory framework in the Russian Federation for the possibility of audio recording and video surveillance installation in a medical organization, as well as the legal justification for banning audio-video recording by a patient in a medical organization.
Keywords: audio recording; video recording; image of a citizen; personal data; information of limited access; personified data recording; medical organization